Endocrine-related factors and risk of venous thromboembolism - Lerstad, Gunhild (UiT The Arctic University of Norway, 2017)
The papers II, III and IV of this thesis are not available in Munin. Paper II: Lerstad, G., Enga, K. F., Jorde, R., Brodin, E. E., Svartberg, J., Brækkan, S. K., Hansen, J-B.: “Thyroid function, as assessed by TSH, and future risk of venous thromboembolism: the Tromsø study”. Available in Eur J Endocrinol 2015, 173:83-90. Paper III: Brodin, E., Lerstad, G., Grimnes, G., Brækkan, S. K., Vik, A., Brox, J., Svartberg, J., Jorde, R., Hansen, J-B.: “Serum levels of vitamin D are not associated with future risk of venous thromboembolism. The Tromsø Study”. Available in Thromb Haemost. 2013 May;109(5):885-90. Paper IV: Lerstad, G., Brodin, E., Svartberg, J., Jorde, R., Brox, J., Brækkan, S. K., Hansen, J-B.: “Associations between serum levels of calcium, parathyroid hormone and future risk of venous thromboembolism -The Tromsø study”. (Manuscript). Even though many environmental and inherited predisposing factors have been associated with venous thromboembolism (VTE), still 30–50% of the events have no obvious provoking factors. There is limited knowledge concerning the association between endocrine-related factors and VTE risk. Therefore we aimed to investigate the relation between hyperglycemia, thyroid function, vitamin D, calcium, parathyroid hormone (PTH), and risk of future VTE in a general population. Our study participants were recruited from the Tromsø study (Tromsø 4; 1994-95, Tromsø 5; 2001-2, and/or Tromsø 6; 2007-8). Two of the papers are based on all three surveys, one paper is based on the fourth and fifth, and one on the fourth survey only. The fourth survey is the largest one, and a total of 27 158 men and women attended. A subset of participants (n=9 056) were further invited to a more extensive second visit. In Tromsø 5 and 6 only subgroups of the municipality of Tromsø were invited. The overall attendance rate went from 77% in Tromsø 4 to 66% in Tromsø 6. Incident VTE events were registered from the date of inclusion until the end of follow-up. Our findings suggest that hyperglycemia does not play ...